Efficacy and safety of second‐line chemotherapy for patients with advanced non‐small cell lung cancer complicated by interstitial lung disease. Issue 21 (15th September 2022) - Otsuka, Kenji; Nokihara, Hiroshi; Mitsuhashi, Atsushi; Ozaki, Ryohiko; Yabuki, Yohei; Yoneda, Hiroto; Ogino, Hirokazu; Nishioka, Yasuhiko
Abstract: Background: Treatment of non‐small cell lung cancer (NSCLC) patients with interstitial lung disease (ILD) is limited because of the risk of its acute exacerbation (AE). Furthermore, the efficacy and safety of second‐line chemotherapy for these patients is unclear. Methods: To investigate the efficacy and safety of second‐line chemotherapy for NSCLC patients with ILD, we retrospectively reviewed patients who were treated at our institute between April 2010 and December 2018. Results: Thirty‐five patients received two or more regimens. Thirty‐four patients were male and the median age at the initiation of second‐line chemotherapy was 70 years. Almost all patients had a smoking history. Fourteen patients had adenocarcinoma and 15 had squamous cell carcinoma histology. Stages III and IV were observed in 20 and 11 patients, respectively. With respect to the type of ILD, 12 patients had usual interstitial pneumonia (UIP). The overall response rate and disease control rate were 11.4 and 68.6%, respectively. The median progression‐free and median overall survival were 4.1 and 6.4 months, respectively. The AE of ILD was observed in eight patients, five of whom died. UIP and low percentage vital capacity were detected as significant risk factors for the AE of ILD. Conclusion: Second‐line chemotherapy among patients with NSCLC complicated by ILD showed a certain effectiveness, but some patients experienced the AE of ILD, which may lead to death. The risk of the AE of ILD must be considered especially for patients with UIP and low percentage VC. Abstract : Interstitial lung disease (ILD) is a limiting factor in the treatment of lung cancer patients. The efficacy and safety of second‐line chemotherapy for this population is unclear. We retrospectively analyzed it among 35 patients who underwent two or more regimens of chemotherapy. A certain efficacy was shown but some patients experienced AEs of ILD that led to death.